Niat Beli Konsumen Pada Produk Bedak Padat Two Way Cake Wardah Di Kota Bandung - Silvi Putri Yustiani; Ida Farida Oesman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the influence of brand ambassadors and halal awareness on consumer purchase intentions on Wardah's two-way cake solid powder products in Bandung City both partially and simultaneously using quantitative verification methods. A total of 385 respondents were involved in this study. The results of the validity test show r count > r table 0.098 is said to be valid. Simultaneous significant results test F showed an F value of 242,428 > F table of 3.04 that the variables of brand ambassador and halal awareness simultaneously had a positive and significant influence on purchase intent. Meanwhile, the results of the partial significant test t show that the value of t is calculated > t table 1,625 that the variables of brand ambassador and halal awareness have a partially significant positive effect on purchase intention. Keywords: Brand Ambassador, Halal Awareness, Purchase Intention